Alternative globalizations : Eastern Europe and the postcolonial world - Mark, James; Kalinovsky, Artemy M.; Marung, Steffi (Indiana University Press, Office of Scholarly Publishing, Herman B Wells Library, 2020)
"Globalization has become synonymous with the seemingly unfettered spread of capitalist multinationals, but this focus on the West and western economies ignores the wide variety of globalizing projects that sprang up in the socialist world as a consequence of the end of the European empires. This collection is the first to explore alternative forms of globalization across the socialist world during the Cold War. Gathering the work of established and upcoming scholars of the Soviet Union, Eastern Europe, and China, Alternative Globalizations addresses the new relationships and interconnections which emerged between a decolonizing world in the post-war period and an increasingly internationalist eastern bloc after the death of Stalin. In many cases, the legacies of these former globalizing impulses from the socialist world still exist today. Divided into four sections, the works gathered examine the economic, political, developmental, and cultural aspects of this exchange. In doing so, the authors break new ground in exploring this understudied history of globalization and provide a multifaceted study of an increasing post-war interconnectedness across a socialist world"--